Active Constituents from Liriope platyphylla Root against Cancer Growth In Vitro. (16th May 2013) - Wang, Hui-Chun; Wu, Chin-Chung; Cheng, Ti-Sheng; Kuo, Ching-Ying; Tsai, Yu-Chi; Chiang, Shang-Yu; Wong, Teng-Song; Wu, Yang-Chang; Chang, Fang-Rong
Abstract : Liriope spicata is a well-known herb in traditional Chinese medicine, and its root has been clinically demonstrated to be effective in the treatment of metabolic and neural disorders. The constituents isolated from Liriope have also recently been shown to possess anticancer activity, although the mechanism of which remains largely unknown. Here, we illustrate the anticancer activity of LPRP-9, one of the active fractions we fractionated from the Liriope platyphylla root part (LPRP) extract. Treatment with LPRP-9 significantly inhibited proliferation of cancer cell lines MCF-7 and Huh-7 and down-regulated the phosphorylation of AKT. LPRP-9 also activates the stress-activated MPAK, JNK, p38 pathways, the p53 cell-cycle checkpoint pathway, and a series of caspase cascades while downregulating expression of antiapoptotic factors Bcl-2, Bcl-XL, and survivin. Such activities strongly suggest a role for LPRP-9 in apoptosis and autophagy. We further purified and identified the compound (−)-Liriopein B from LPRP-9, which is capable of inhibiting AKT phosphorylation at low concentration. The overall result highlights the anticancer property of LPRP-9, suggests its mechanism for inhibition of proliferation and promotion of cell death for cancer cells via regulation of multitarget pathways, and denotes the importance of purifying components of fraction LPRP-9 to aid cancer therapy.